The Dark Side of Communication Studies in Higher Education of Indonesia - Masduki Masduki (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2022)
This paper revisits the academic culture of Communication studies in Indonesia, which has been stagnant since the political tragedy of 1998 to 2021. The autocratic political system of the New Order, on the one hand, and the liberalization of education, on the other, have triggered it, resulting in the phenomenon of ‘dark academia’. This paper wants to address this research question: how is the portrait of communication studies in Indonesia during the last decade? Data were extracted from the collaborative research findings using qualitative methods, organized by the Central Committee of ASPIKOM for the period 2019-2022. The data primarily are generated from the profiles of Communication study program filled out by the ASPIKOM members, as well as from the unstructured interviews and analysis of government policies. This paper finds stagnation in the discipline of Communication studies, particularly the domination of these three special disciplines: Communication science, Public Relations, and Journalism. A combination of bureaucracies in higher education and the global-digital scale of knowledge capitalism hindered academic autonomy and knowledge production within communication sholars.